Social and rhetorical references in Nisheh's balcony of the poet Ibrahim al-Buhrzi (Journal of the College of Basic Education, 2022)
Signs are linguistic signs whose reference is determined only by the context in which they were said; Because it is devoid of any meaning in itself, that is why our ancient Arab scholars used to call it (the ambiguities), and the research wanted from this aspect to explain the roots of the concept of denotations in the Arab linguistic heritage and its rooting to highlight the features of descriptive descriptive expressions in the treatises and directives of the ancients and how to use them, and by looking at the Diwan “Nitsha’s Balcony” by the poet Ibrahim al-Buhrzi and his grandmother has used social denotations in abundance in most of his poems, because they are structures and words that indicate the type of relationship between the speakers. This is because in every text there are personal, temporal, spatial and social denotations. The use of rhetorical and social denotations helped the poet to express his different intentions through our extrapolation of their use. It revealed the dimensions of his relationship with the addressees and their difference from one poem to another, as he does not address everyone in the same language, but differs from place. to another and from time to time.